Fetal programming pathway from maternal mental health to infant cortisol functioning: The role of placental 11β-HSD2 mRNA expression. (May 2021) - Galbally, Megan; Watson, Stuart J.; Lappas, Martha; de Kloet, E. Ron; van Rossum, Elisabeth; Wyrwoll, Caitlin; Mark, Peter; Lewis, Andrew J.
Abstract: Placental 11β-HSD2 has been a focus of research for understanding potential fetal programming associated with maternal emotional disorders. This study examined the pathway from antenatal mental health via placental 11β-HSD2 mRNA to cortisol regulation in the infant offspring. This study reports on data obtained from 236 participants in the Mercy Pregnancy and Emotional Wellbeing Study (MPEWS). At term, placental tissue was collected within 30 min of birth from 52 participants meeting current criteria for a depressive disorder, and 184 control participants. Depressive disorders were diagnosed using the SCID-IV. In addition, antidepressant use, depressive and anxiety symptoms were measured in early and late pregnancy. Placental 11β-HSD2 mRNA expression was measured using qRT-PCR. Infant salivary cortisol samples were taken at 12 months of age. Women on antidepressant medication and with higher trait anxiety had higher placental 11β-HSD2 expression compared to women not taking medication. Furthermore, the offspring of women taking an antidepressant and who also had a current depressive disorder and high trait anxiety had high cortisol reactivity at 12 months of age and this was mediated through 11β-HSD2 mRNA expression. In contrast, offspring of women not taking antidepressant medication with depressive disorder and high anxiety there was low cortisol reactivity observed. Our findings suggest that the relationship between maternal antenatal depression and anxiety and infant cortisol reactivity is mediated through placental 11β-HSD2 mRNA expression. Furthermore, the direction differed for women taking antidepressants, where infant cortisol reactivity was high whereas when compared to those with unmedicated depression and anxiety, where infant cortisol reactivity was low. Highlights: There has been substantial research understanding placental role in fetal programming pathways for maternal mental health. Placental 11β-HSD2 has one area of focus given the role in cortisol regulation across the placenta. Placental 11β-HSD2 mRNA expression in this study was found to be lower in those with depression and anxiety. This study also found that antidepressant use increased placental 11β-HSD2 mRNA expression. Infant cortisol reactivity was mediated through 11β-HSD2 mRNA expression and this differed by mental health and antidepressants use.